Risk Factor That Influence Sexual Behavior on Adolescents in Bekasi City - Heriza Syam; Winancy; Siti Masitoh (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2022)
Background : Teenagers in Indonesia aged 10-19 years, 79.5% of whom are internet users, 52% have found pornographic content, either through advertisements or sites that do not offer it and 14% who claim to have accessed pornographic content voluntarily. Megan et al stated that the increased frequency of use of social media the greater the likelihood of having sex. Purpose: to analyze risk factor that influence sexual behavior in adolescents. Methods The mixed methods research methodology combines qualitative and quantitative research. The research design is a concurrent embedded design, collecting quantitative and qualitative data at one time, where qualitative data serves as a support. The research sample is 100 people. Univariate and bivariate analysis with Spearman correlation test. Result : There’a 55 % of youth in bekasi enagage in risk sexual behavior. there are differences in risk sexual behavior between male and female adolescents (p=0.049), negative influence from peers (p=0.002) and less harmonious family (p=0.004) on the occurrence of risky sexual behavior. There is a relationship between the frequency of using social media (p=0.033) and the length of time using social media (p=0.013); with risky sexual behavior Risk sexual behavior begins with nasty chats, then continues with nude videos that eventually lead to premarital sex. Conclusion: Boys are more likely to engage in risk sexual behavior than girls in Bekasi City. Peers and families who are less harmonious contribute to the occurrence of risk sexual behavior in adolescents. Unwise use of social media tends to have a negative effect on increasing risk sexual behavior.